The Effectiveness of Think Talk Write Models on Student Motivation and Thinking Ability - Siwi, Laras Grahita; Sugiyo, Sugiyo; Utomo, Udi (Universitas Negeri Semarang, 2021)
The ability to think critically is an important component in facing the era of society 5.0. There needs an effort to optimize these abilities for students in the context of learning in elementary schools. The purpose of this study was to analyze the effectiveness of the Think Talk Write (TTW) cooperative learning model on students' motivation to learn high-order thinking skills. The type of research used is quantitative research with a quasi-experimental type. Data collection techniques used higher-order thinking skills tests, questionnaires, interviews, and documentation. The data analysis uses quantitative analysis techniques. Quantitative data analysis techniques include independent sample t-test and paired sample t-test. The research subjects were 76 students. The results showed that the TTW type of cooperative model was effective against learning motivation and higher-order thinking skills. This is indicated by the higher-order thinking average score in the experimental class is higher than the average score in the control class. This research concludes is that learning with the TTW cooperative model is effective and has a positive effect on students' learning motivation and higher-order thinking